1999
DOI: 10.1104/pp.120.3.879
|View full text |Cite
|
Sign up to set email alerts
|

Limonene Synthase, the Enzyme Responsible for Monoterpene Biosynthesis in Peppermint, Is Localized to Leucoplasts of Oil Gland Secretory Cells1

Abstract: Circumstantial evidence based on ultrastructural correlation, specific labeling, and subcellular fractionation studies indicates that at least the early steps of monoterpene biosynthesis occur in plastids. (4S)-Limonene synthase, which is responsible for the first dedicated step of monoterpene biosynthesis in mint species, appears to be translated as a preprotein bearing a long plastidial transit peptide. Immunogold labeling using polyclonal antibodies raised to the native enzyme demonstrated the specific loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(124 citation statements)
references
References 53 publications
5
114
0
5
Order By: Relevance
“…The rate of monoterpene biosynthesis determined by 14 CO 2 pulse labeling (Gershenzon et al, 1999) has been shown to rise rapidly in newly emerging leaves, reaching a sharp peak between 12 and 20 d, and then rapidly declining as full leaf expansion is reached (Fig. 2A).…”
Section: Developmental Regulation Of Monoterpene Biosynthetic Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…The rate of monoterpene biosynthesis determined by 14 CO 2 pulse labeling (Gershenzon et al, 1999) has been shown to rise rapidly in newly emerging leaves, reaching a sharp peak between 12 and 20 d, and then rapidly declining as full leaf expansion is reached (Fig. 2A).…”
Section: Developmental Regulation Of Monoterpene Biosynthetic Activitymentioning
confidence: 99%
“…This pattern of development in monoterpene biosynthetic capability and accumulation is entirely consistent with the population dynamics of the peltate oil glands, which pass through the one-, two-, four-, and eight-celled stages and complete oil secretion prior to full leaf expansion (G. Turner, J. Gershenzon, and R. Croteau, unpublished data). Since neither monoterpene catabolism (Mihaliak et al, 1991) nor monoterpene volatilization contribute significantly to alterations in the level of stored product (Gershenzon et al, 1999), the pattern of monoterpene accumulation in peppermint glandular trichomes appears to chiefly reflect the rate of biosynthesis.…”
Section: Developmental Regulation Of Monoterpene Biosynthetic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Total lipids and terpenes were abundantly stained by the histochemical tests in the morphotype I, mainly in the head cells. In fact, the observation of several plastids lacking thylakoids in the head cells is associated with the production of oils (Fahn 1979;Rodrigues & Machado 2012); in addition, the presence of tubular inclusions in these plastids is common reported in cells secreting monoterpenes (Turner et al 1999). In general way, lipids are released from the secretory cells via ecrine (Evert 2006), cross the cell wall driven by the mechanical pressure exercised by the protoplast (Paiva 2016) and accumulate in the subcuticular space; oil material can cross the cuticle and reach the outer side of the cells without requiring rupture of pore formation in the cuticle.…”
Section: Discussionmentioning
confidence: 99%